Pengaruh Perencanaan Anggaran, Pelaksanaan Anggaran, dan Regulasi Terhadap Penyerapan Anggaran pada Satker di Wilayah Hukum Pengadilan Tinggi Riau (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Optimal budget absorption is an important indicator of effective public financial management, but judicial work units still face various obstacles. This study aims to analyze the influence of budget planning, budget execution, and regulations on budget absorption in work units within the jurisdiction of the Riau High Court. The study used a quantitative approach with a causal design. The sample was determined using a saturated sampling technique (total sampling) so that the entire population consisting of 55 employees involved in financial management were used as respondents. Data were collected through questionnaires and analyzed using multiple linear regression. The results showed that budget planning and budget execution had a positive and significant effect on budget absorption, while regulations had a negative but insignificant effect. This finding indicates that the success of budget absorption is more determined by the quality of planning and implementation effectiveness than the existence of regulations alone. The insignificance of regulations indicates that changes or complexity of rules have not directly affected budget absorption when work units already have adaptive implementation mechanisms. Simultaneously, all three variables have a significant effect on budget absorption. This study confirms that implementation capacity is a more determining factor than regulatory aspects in improving financial management performance in judicial institutions.